PENGARUH PEMBINAAN PROFESIONALISME TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SUNGAI PENUH - GUSMITA, EMILYA (journal of RESIDU, 2018)
The title of this research is the relationship of organizational support with work attitude of clerk office Camat Gunung Kerinci. This research aims to see the relationship of organizational support with employee work attitude at the office Camat Gunung Kerinci. Research method used in this research is quantitative method, because the researcher wants measurement between variable X and variable Y. The sample in this study was thirty five people. The technique used in the determination of respondents is saturated sampling while the research instrument in the form of, hypothesis test analysis techniques, with the results of research can be seen 7.506 >  2.0345  so Ha accepted Ho in rejection. Meaning that organizational support has a significant relationship with work attitude at the sub district office Camat Gunung Kerinci.